PELATIHAN DIVERSIFIKASI PRODUK KULIT BUAH PALA MENJADI SIRUP PALA UNTUK MENINGKATKAN PENDAPATAN KELUARGA PETANI - Tienni Mariana Simanjorang; Martha Turukay; Leonard O. Kakisina; Nafly Comilo Tiven (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Tamilouw Village in Amahai District, Central Maluku Regency, is one of the main nutmeg-producing areas. However, the farmers there have not used nutmeg peels to be processed into high-value products like nutmeg syrup. In fact, nutmeg syrup can be an additional source of income for the family, apart from the nutmeg farming business itself. For this reason, a service program was held that aimed at providing counseling, technical training, production assistance, and explanations of nutmeg syrup marketing strategies. In this program, housewives involved in nutmeg farming showed high enthusiasm. They actively participate in training, which provides them with new knowledge and skills in processing nutmeg peels into syrup. This training not only increases their capacity in nutmeg syrup production, but also provides insight into how to market the product. With this program, farmers and families in Tamilouw Village can take advantage of the full potential of nutmeg plants, so that they do not only depend on nutmeg seed yields. As a result, nutmeg farming housewives now have better abilities in making and marketing nutmeg syrup, which has the potential to increase family income and the village economy as a whole.